Akira Kurosawa's dreams - Ikebe, Shin'ichirō 1943-
Eight episodes exploring many aspects of humankind and man's need to harmonize with nature. Based on Akira Kurosawa's actual dreams.
Enth. Bonusmaterial
Orig.: USA, Japan 1990
Keywords: Shizen - Dorama; Naturaleza - Teatro; Human beings -- Effect of environment on -- Drama; Nature -- Effect of human beings on -- Drama; Anthology films; Feature films; Fiction films; Foreign films; Video recordings for the hearing impaired; Foreign language films - Japanese